PCI compliance : implementing effective PCI data security standards - Bradley, Tony, 1969-; Burton, James D. (Syngress, 2007)
Identity theft has been steadily rising in recent years, and credit card data is one of the number one targets for identity theft. With a few pieces of key information. Organized crime has made malware development and computer networking attacks more professional and better defenses are necessary to protect against attack. The credit card industry established the PCI Data Security standards to provide a baseline expectancy for how vendors, or any entity that handles credit card transactions or data, should protect data to ensure it is not stolen or compromised. This book will provide the information that you need to understand the PCI Data Security standards and how to effectively implement security on the network infrastructure in order to be compliant with the credit card industry guidelines and protect sensitive and personally identifiable information. *PCI Data Security standards apply to every company globally that processes or transmits credit card transaction data *Information with helps to develop and implement an effective security strategy to keep their infrastructure compliant *The authors are well known and each has an extensive information security background, making them ideal for conveying the information the reader needs.